KERUPUK: PRODUK TURUNAN DARI PETERNAKAN IKAN LELE MASYARAKAT DI DESA AGUNG KOTO IMAN - Alwi, Ikhza; Tiara, Tiara; Ditama, Rezki Agrisa; Angela, Lia (Institut Agama Islam Negeri Kerinci, 2023)
Catfish is one type of fish that is widely cultivated by the community in Agung Village, Kerinci Regency. To increase its selling value, it is necessary to design a derivative product so that catfish can be known in other forms, such as Amplang catfish. This study describes catfish derivative products and their promotion in the community of Agung Village. The results of the activity show that catfish amplang needs to be developed into flavor variants and product marketing analysis.